The microtubule-severing enzyme spastin regulates spindle dynamics to promote chromosome segregation in Trypanosoma brucei - Thiago Souza Onofre; Qing Zhou; Ziyin Li (Communications Biology)
Abstract Microtubule-severing enzymes play essential roles in diverse cellular processes, including mitosis and cytokinesis, by modulating microtubule dynamics. In the early branching Trypanosoma brucei, microtubule-severing enzymes are involved in cytokinesis and flagellum length control, but none of them have been found to regulate mitosis. Here we report the characterization of the microtubule-severing enzyme spastin in the procyclic form of T. brucei. We demonstrate that spastin severs microtubule in vitro and overexpression of spastin disrupts spindle microtubules in vivo in trypanosomes, leading to defective chromosome segregation. Knockdown of spastin impairs spindle integrity and disrupts chromosome alignment and segregation. We further show that the function of spastin requires the catalytic AAA-ATPase domain, the microtubule-binding domain, and the microtubule interacting and trafficking domain, and that the association of spastin with spindle depends on the microtubule-binding domain. Together, these results uncover important roles for spastin in chromosome segregation by regulating spindle dynamics in T. brucei.